“The Disabled Community Is Still Waiting for Equality”: What do Users Have to say About Sexual Reproductive Health of Persons With Disabilities in Online News Comments - Abwao, Mauryne; Ittefaq, Muhammad; Baines, Annalise; Liu, Pan (Frontiers in Communication, 2021)
Drawing from the literature of the internet as a public sphere, the present study investigates online news comments related to sexual reproductive health of people with disabilities (PWDs) published in The New York Times and The Guardian. We analyzed 3,633 online comments published between January 1, 2016, and December 31, 2019, using thematic analysis. The findings revealed eight major themes: economic consequences; gender; stereotypes; awareness and education; independence and autonomy; medical standpoint; media portrayal; and social justice and accommodation. Further, our study found that 47% of online commenters from The NYT and 49.3% from The Guardian had a positive perception that PWDs should have equal access to sexual reproductive health, compared with non-disabled people. Our study also revealed that comments in The NYT were more focused on the legal issues in the United States, while comments in The Guardian emphasized positive media representation and human aspects of the issue.